Kaveri Special - Kaveri Special (yhtye); Adje, Felix; Chime, Ike; Kivistö, Kimmo; Palonen, Tuomas; Puisto, Tino; Renvall, Jonne (Kaveri Special, 2014)
8 kappaletta.
Keywords: Kaveri Special (yhtye) : albumit